2020
DOI: 10.1111/dth.13383
|View full text |Cite
|
Sign up to set email alerts
|

A case of exacerbation of psoriasis after oseltamivir and hydroxychloroquine in a patient with COVID ‐19: Will cases of psoriasis increase after COVID ‐19 pandemic?

Abstract: China and spread around the world. 1 The new type of SARS-Cov2, a mutant novel coronavirus that humans encountered for the first time, binds to ACE receptors cause pneumonia. Researchers have focused on the treatment of the current disease through different pathways, especially this pathophysiological mechanism besides FcR activation. 2 Recent studies have revealed numerous effective therapeutic options including favipiravir, brincidofovir, monoclonal antibodies, hydroxychloroquine, oseltamivir, and antisense … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
81
0
5

Year Published

2020
2020
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(89 citation statements)
references
References 9 publications
3
81
0
5
Order By: Relevance
“…The anxiety associated with the actual COVID-19 infection, as well as with the isolation and social distancing that people have to experience due to the pandemic, can be a potential cause for exacerbation of several chronic inflammatory skin conditions, especially those which are stress induced, like psoriasis, atopic dermatitis, rosacea and urticaria (35). Medication adherence, especially in psoriasis has been challenging (36), and could potentially deteriorate in the midst of the current COVID-19 panic and misinformation in the social media (37), therefore providing clear guidance through efficient patient-clinician communication is of critical importance.…”
Section: Dermatologymentioning
confidence: 99%
“…The anxiety associated with the actual COVID-19 infection, as well as with the isolation and social distancing that people have to experience due to the pandemic, can be a potential cause for exacerbation of several chronic inflammatory skin conditions, especially those which are stress induced, like psoriasis, atopic dermatitis, rosacea and urticaria (35). Medication adherence, especially in psoriasis has been challenging (36), and could potentially deteriorate in the midst of the current COVID-19 panic and misinformation in the social media (37), therefore providing clear guidance through efficient patient-clinician communication is of critical importance.…”
Section: Dermatologymentioning
confidence: 99%
“…As a result, many national and international societies proposed specific recommendations to help both physicians and patients to face the pandemic (10-13). Although cases of psoriasis exacerbation in COVID-19 infected patients have been reported (14,15), little is known about how the pandemic-related lockdown has influenced the life of COVID-19 negative psoriatic patients. The aim of this study was to describe the impact of the lockdown during the COVID-19 pandemic in a cohort of Italian psoriatic patients treated with biological therapies, analyzing the clinical course of the disease, therapy management and patients' psychological status.…”
Section: Introductionmentioning
confidence: 99%
“…changes are also reflected in dermatology outpatient and inpatient clinics. 2,3 Recently, we reported that not number but percentages of patients with scabies, psoriasis, urticaria, and scabies-related visits to dermatology outpatient clinic increased immediately 10 days after COVID-19 pandemic. 4 However, we observed a sudden rise in the number of scabies two months after the first case of COVID-19 in Turkey.…”
mentioning
confidence: 99%